Generation & characterization of expandable human liver sinusoidal endothelial cells and their application to assess hepatotoxicity in an advanced in vitro liver model. (1st January 2023) - Kaden, Tim; Noerenberg, Astrid; Boldt, Jennifer; Sagawe, Carolin; Johannssen, Timo; Rennert, Knut; Raasch, Martin; Evenburg, Torge
Abstract: Liver sinusoidal endothelial cells (LSECs) are highly specialized endothelial cells forming the hepatic sinusoidal wall. Besides their high endocytic potential, LSECs have been demonstrated to markedly contribute to liver homeostasis and immunity, and may partially explain unexpected hepatotoxicity of drug candidates. However, their use for in vitro investigations is compromised by poor cell yields and a limited proliferation capacity. Here, we report the transient expansion of primary human LSECs from three donors by lentiviral transduction. Transduced ("upcyte®") LSECs were able to undergo at least 25 additional population doublings (PDs) before growth arrest due to senescence. Expanded upcyte® LSECs maintained several characteristics of primary LSECs, including expression of surface markers such as MMR and LYVE-1 as well as rapid uptake of acetylated LDL and ovalbumin. We further investigated the suitability of expanded upcyte® LSECs and proliferating upcyte® hepatocytes for detecting acetaminophen toxicity at millimolar concentrations (0, 0.5, 1, 2, 5, 10 mM) in static 2D cultures and a microphysiological 3D model. upcyte® LSECs exhibited a higher sensitivity to acetaminophen-induced toxicity compared to upcyte® hepatocytes in 2D culture, however, culturing upcyte® LSECs together with upcyte® hepatocytes in a co-culture reduced APAP-induced toxicity compared to 2D monocultures. A perfused Dynamic42 3D model was more sensitive to acetaminophen than the 2D co-culture model. Cytotoxicity in the 3D model was evident by decreased cellular viability, elevated LDH release, reduced nuclei counts and impaired cell morphology. Taken together, our data demonstrate that transient expansion of LSECs represents a suitable method for generation of large quantities of cells while maintaining many characteristics of primary cells and responsiveness to acetaminophen.